Surviving the FDACS Bureau of Compliance Monitoring Inspection: Walking through an Inspection - Frederick M. Fishel (EDIS)
PI-158, a 13-page illustrated fact sheet by Frederick M. Fishel, assists agricultural producers in preparing for the day when the inspector arrives at their operation. It reviews the elements that an inspector for the Florida Department of Agriculture and Consumer Services (FDACS) Bureau of Compliance Monitoring (BCM) will examine during a routine agricultural establishment inspection. Includes references and copies of related forms. Published by the UF Department of Agronomy, November 2007.